EpCAM aptamer mediated cancer cell specific delivery of EpCAM siRNA using polymeric nanocomplex - Nithya Subramanian; Jagat R. Kanwar; Prasanna kumar Athalya; Narayanan Janakiraman; Vikas Khetan; Jagat R. Kanwar; Sailaja Eluchuri; Subramanian Krishnakumar (2015)
Abstract Background Epithelial cell adhesion molecule (EpCAM) is overexpressed in solid tumors and regarded as a putative cancer stem cell marker. Here, we report that employing EpCAM aptamer (EpApt) and EpCAM siRNA (SiEp) dual approach, for the targeted delivery of siRNA to EpCAM positive cancer cells, efficiently inhibits cancer cell proliferation. Results Targeted delivery of siRNA using polyethyleneimine is one of the efficient methods for gene delivery, and thus, we developed a novel aptamer-PEI-siRNA nanocomplex for EpCAM targeting. PEI nanocomplex synthesized with EpCAM aptamer (EpApt) and EpCAM siRNA (SiEp) showed 198 nm diameter sized particles by dynamic light scattering, spherical shaped particles, of 151 ± 11 nm size by TEM. The surface charge of the nanoparticles was −30.0 mV using zeta potential measurements. Gel retardation assay confirmed the PEI-EpApt-SiEp nanoparticles formation. The difference in size observed by DLS and TEM could be due to coating of aptamer and siRNA on PEI nanocore. Flow cytometry analysis revealed that PEI-EpApt-SiEp has superior binding to cancer cells compared to EpApt or scramble aptamer (ScrApt) or PEI-ScrApt-SiEp. PEI-EpApt-SiEp downregulated EpCAM and inhibited selectively the cell proliferation of MCF-7 and WERI-Rb1 cells. Conclusions The PEI nanocomplex fabricated with EpApt and siEp was able to target EpCAM tumor cells, deliver the siRNA and silence the target gene. This nanocomplex exhibited decreased cell proliferation than the scrambled aptamer loaded nanocomplex in the EpCAM expressing cancer cells and may have potential for EpCAM targeting in vivo .